Kepemimpinan Keselamatan, Komitmen Ahli K3, Akuntabilitas Terhadap Kepuasan Kerja dan Kinerja Keselamatan - Tatan Sukwika; Gatot Sutrisno (LPPM Universitas BSI, 2021)
ABSTRACTThe incidence of work accident rates tends to be volatile due to ineffective patterns of cooperation and communication between employees and leaders understanding OHS. The purpose of this study is to examine safety leadership, the commitment of OHS experts, accountability to job satisfaction & safety performance. The research analysis method used the PLS or partial least square modeling test. Data collection using questionnaire answer results with a sample of 99 employees. The results show that job satisfaction is significantly affected by safety leadership, and OHS expert commitment and responsibility and safety performance are affected by safety leadership and job satisfaction. The variable commitment and accountability of OHS experts have no significant impact on company performance. The conclusion found workers were satisfied that safety leadership, OHS expert commitments, and accountability could be applied, resulting in improved safety performance. On the other hand, OHS experts have no commitment and accountability to improve safety performance. This situation is due to workers' lack of commitment to implementing OHS and accountabilities. Managerial implications require the OHS aspect to be an integral part of the company's operations and the consequences for improving safety performance standards. Keywords: leadership, OHS expert, accident, accountability, performance